2018
DOI: 10.15171/jlms.2018.30
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Quorum-Sensing and Efflux Pumps Interactions in Pseudomonas aeruginosa Against Photooxidative Stress

Abstract: Quorum SensingCommunication between similar or different species occurs via various chemical signals produced and secreted by the bacteria. These signals can be population dependent (QS) or can be secreted during several proliferation stages (e.g., indole, which is secreted in the stationary phase by Escherichia coli). AbstractResistant infections essentially cause mortality in a burn unit. Several bacteria contribute to burn infections; among these, Pseudomonas aeruginosa majorly contributes to these infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…Several studies have shown that cell-to-cell communication and regulation of numerous virulence factors in bacteria are managed by QS systems [32][33][34][35][36]. In Staphylococcus aureus, the Agr system controls the production and dissemination of biofilm, consequently, inducing both acute and chronic biofilm-associated infections [36].…”
Section: Quorum Sensing and Pathogenicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that cell-to-cell communication and regulation of numerous virulence factors in bacteria are managed by QS systems [32][33][34][35][36]. In Staphylococcus aureus, the Agr system controls the production and dissemination of biofilm, consequently, inducing both acute and chronic biofilm-associated infections [36].…”
Section: Quorum Sensing and Pathogenicitymentioning
confidence: 99%
“…The LasI is one of the major mechanisms of pathogenicity and resistance of Pseudomonas aeruginosa. It regulates the biofilm formation, and virulence factors such as exotoxin A, elastase, pyocyanin, alkaline phosphatase, and rhamnolipid [35]. Similarly, Bacillus cereus virulence factors, such as phospholipases C, proteases and hemolysins, are controlled by the expression of QS system [38].…”
Section: Quorum Sensing and Pathogenicitymentioning
confidence: 99%
“…P. aeruginosa has complex regulatory systems, which allow it to combat environmental stressors with the use of different mechanisms; e.g., in the presence of an antibiotic, cells could use efflux pumps [ 4 ] or form biofilm [ 5 ]. The multilevel regulatory network allows P. aeruginosa to modulate the metabolism to endure different stress conditions e.g., heat shock [ 6 ], the presence of antimicrobials [ 7 ], photooxidative [ 8 ], or osmotic stress [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…CS is a cell-tocell signaling mechanism that coordinates a range of behaviors at the population level [7]. CS is a mechanism by which the bacterium censes the microbial density present through the production of N-acyl homoserine lactone-like molecules, which function as autoinducers that bind with receptor proteins to form a complex that in turn favors the expression of genes that code for the production of more N-acyl-homoserine lactone synthase and the receptor itself, thus forming circuit mechanisms in las and rhl series, in which, consequently, the expression of virulence factors such as elastase, protease, pyocyanin will begin with which the bacteria will begin biofilm synthesis to contribute to its adhesion and infection progress [8]. Finally, there is a third molecule of CS, which is the so-called autoinducer-3 (AI-3), which involves signaling between taxonomic domains, that is, between bacteria and archaea (prokaryotic cells), and eukaryotes (organisms higher).…”
Section: Introductionmentioning
confidence: 99%